CULTURE OF PERSONALITY PERTAINING TO THE HUMANITIES: SOCIO-PHILOSOPHICAL ASPECT - M. E. Kudryavtseva (Дискурс)
Culture pertaining to the humanities is associated with knowledge and exploration of human intellectual and spiritual phenomena that can help the further development of his personality and integration to the human community. Culture of personality pertaining to the humanities is not a static formation, it is formed and constantly renewed in a certain problem field of human activity. Culture pertaining to the humanities is included in the concept of professional culture ensuring its component pertaining to the humanities; professional culture constitutes one pertaining to the humanities as a set for creative and socially-responsible professional activity by a person.